The Hotel Boom And Urban Transformation: Spatial Patterns In Yogyakarta Urban Area - Kamal Setiawan; Yusliana; Candra Ragil (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
The increasing number of hotels has a significant impact on spatial development in the Yogyakarta Urban Area (YUA). The concentrated distribution of hotels in urban areas triggers spatial changes and encourages land conversion. On the other hand, the development of many hotels can put pressure on environmental resources. This study aims to analyze the spatial pattern of hotels in the YUA. Quantitative analysis techniques are used with primary and secondary data sources by collecting secondary data and conducting field observations. The approach used is a spatial-temporal approach by interpreting images and overlay techniques obtained multitemporally with a time span of 5 (five) years from 2018 to 2022. The population in this study includes all hotels in YUA, including starred and non-starred hotels. The analytical methods used are nearest-neighbor analysis (NNA) and Density Kernel. The results of this study indicate that the distribution pattern of hotels in YUA in 2018 & 2022 is clustered, and the direction of hotel development in the YUA is to the northeast or towards Depok District. It can be concluded that hotel distribution not only reflects tourism development but also contributes to spatial transformation by reorienting spatial functions and driving urban expansion.